Bioactive Paper Coated with Green Synthesized Silver/iron Oxide for Food Packaging - Jittham, Rawit; Kasemsiri, Pornnapa (Srinakharinwirot University Engineering Journal, 2024)
Utilization of antibacterial packaging is an approach to maintain and extend shelf-life of foods. This research aims to develop the bioactive composite paper coating with bioactive compound viz, silver-iron oxide particles (Ag/Fe3O4). Starch waste from cassava starch industry and tannic acid are used as bio reducing agents for synthesis of Ag/Fe3O4. The effect of tannic acid concentration at 0-3 %w/v is studied. Based on the study, the increase of tannic acid concentration for coating of paper enhances tensile strength, water resistance and antibacterial activities i.e. Staphylococcus aureus: S.aureus and Escherichia coli: E.coli. The coated paper with Ag/Fe3O4 at 3% w/v of tannic acid could maintain vitamin C and delay the ripening of tomatoes. Therefore, the obtained packaging had potential to apply as bioactive packaging to maintain food quality and prolong the shelf-life.